2002
DOI: 10.1677/joe.0.1720321
|View full text |Cite
|
Sign up to set email alerts
|

Structurally distinct membrane-associated and soluble forms of GH-binding protein in the mouse

Abstract: It has previously been shown that the large increase in GH-binding capacity of mouse liver microsomes during pregnancy is due largely to an increase in the amount of GH-binding protein (GHBP), with a more modest increase in GH receptor (GHR). Here we show that mouse liver GHBP is predominantly present as a membrane-associated protein structurally distinct from the soluble form of GHBP present in serum. Liver GHBP is associated with both intracellular membranes and the plasma membrane. Membrane-associated GHBP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…2). The MA-GHBP forms from every mouse line studied showed the same molecular weight, which was different from the soluble GHBP molecular forms, corroborating what has been previously described by us and other authors [23,25,26].…”
Section: Mgh Equivalentssupporting
confidence: 90%
See 3 more Smart Citations
“…2). The MA-GHBP forms from every mouse line studied showed the same molecular weight, which was different from the soluble GHBP molecular forms, corroborating what has been previously described by us and other authors [23,25,26].…”
Section: Mgh Equivalentssupporting
confidence: 90%
“…To act as a negative regulator, MA-GHBP needs to be associated with the extracellular surface of the plasma membrane, although not every form of the MA-GHBP is at the extracellular membrane [23,26]. Frick et al [26] have shown that GHBP accounts for 50% of GH binding to plasma membrane of rat adipocytes, but most of MA-GHBP is associated with intracellular membranes, principally with the endoplasmic reticulum [23,43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have demonstrated that mouse liver GHBP is predominantly present as a membrane-associated protein structurally distinct from the soluble form of GHBP present in serum (Cerio et al 2002). Liver GHBP is associated with both intracellular membranes and the plasma membrane.…”
Section: Journal Of Endocrinology (2002) 175 55-59mentioning
confidence: 99%